Layanan referensi virtual perpustakaan Universitas Leiden melalui perpustakaan KITLV-Jakarta - Rizkiana Karmelia Shaura; Tamara Adriani Salim; Hendra Kurniawan (Berkala Ilmu Perpustakaan dan Informasi, 2020)
Introduction. This study discusses Leiden University Library reference services through the KITLV-Jakarta. Since KITLV was acquired by the Leiden University Library, the KITLV-Jakarta Library which was a KITLV-Dutch representative, is now a representative of the Leiden University Library in Jakarta. Data Collection Method. This study used a qualitative approach with descriptive research involving observations and interviews as well as primary document data sources. Data Analysis. The data was analyzed by involving the process of data reduction, interpretation, and conclusion. Results and Discussions. The results of the study indicate that reference services, particularly for reference collections found in the Leiden University Library cannot be accessed directly through the KITLV-Jakarta Library. Only KITLV librarians can request the reference service from Leiden University librarians. Conclusion. Librarians at the KITLV-Jakarta Library do not have the same access as librarians at the Leiden University Library, even though the KITLV-Jakarta Library is a representative of the Leiden University Library in Jakarta.